Conocimientos de las madres sustitutas del ICBF de pasto sobre la discapacidad de los niños (as) a su cargo y las necesidades ocupacionales de los mismos - Delgado Meneses, Sor Sandra Cristina; Criollo Castro, Carlos (Universidad y Salud, 2009)
The article concerns the outcome of a project of Occupational Therapy applied to surrogacy Grass ICBF that are responsible for disabled children at identifying the level of theoretical and practical instruction that have regard to the pathology of children and the relationship versus the occupational needs of children. The work was based on a community-centered approach to spirituality as a central axis, in addition to the proposed new approach to disability offered by the IFC, under a mixed paradigm, with a historical hermeneutic and ethnographic method, identifying the type disability, the degree of independence and functionality present in children and/or girls observed versus the educational level of mothers, theoretical knowledge about the pathology of the child in charge and the interest shown in this aspect Like on more or less effective way to contribute to treatment. These results enabled the development of a proposal of intervention developed by occupational therapists speech and provide treatment from the rating and for joint intervention with the mother.